2017
DOI: 10.15171/jpd.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum phosphorus, calcium and parathyroid hormone with cardiovascular calcification in regular hemodialysis patients

Abstract: Introduction: Dialysis patients tend to have a greater prevalence of cardiovascular diseases. Objectives: The aim of this study was to determine the prevalence of heart valves calcification, left ventricular hypertrophy, and left ventricular systolic and diastolic dysfunction. It also aimed to determining the relationship of the above mentioned parameters with serum calcium, phosphorus, parathormone and duration of dialysis. Patients and Methods: This cross-sectional study was conducted on 100 hemodialysis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The differences can be due to the therapeutic effects of medications given to the patients in various study groups as a part of CKD treatment. In our study, we multiplied calcium by phosphorus in hemodialysis patients and the result was 40 mg 2 /dl 2. In a similar study by Nematollahi [10] it was 44 units. The study of Block et al [20] inferred that every 10 units of Ca×PO4 product increase, the mortality rate of hemodialysis patients increased by 7%.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The differences can be due to the therapeutic effects of medications given to the patients in various study groups as a part of CKD treatment. In our study, we multiplied calcium by phosphorus in hemodialysis patients and the result was 40 mg 2 /dl 2. In a similar study by Nematollahi [10] it was 44 units. The study of Block et al [20] inferred that every 10 units of Ca×PO4 product increase, the mortality rate of hemodialysis patients increased by 7%.…”
Section: Discussionmentioning
confidence: 74%
“…However serum PTH levels were elevated in 70% cases of CKD patients with cardiac abnormalities. Nematollahi et al [10] had found significant positive relationship with the calcification of the heart valves with serum phosphorous. He also found serum phosphorus level had a significant relationship with left ventricular systolic dysfunction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mousavi Movahed et al observed no significant relationship between serum calcium levels with heart disease and the calcification of heart valves (27). However, the results of studies performed by Zand Parsa et al and Nematollahi et al showed a direct linear relationship between calcium levels and the severity of heart disease in these patients (28,29). The difference in sample size in these two studies could cause this discrepancy in the results.…”
Section: Discussionmentioning
confidence: 91%